Early permanent cerebrospinal fluid diversion in aneurysmal subarachnoid hemorrhage: does a lower rate of nosocomial meningitis outweigh the risk of delayed cerebral vasospasm related morbidity?. (2nd January 2021) - Croci, Davide Marco; Dalolio, Martina; Aghlmandi, Soheila; Taub, Ethan; Rychen, Jonathan; Chiappini, Alessio; Zumofen, Daniel; Guzman, Raphael; Mariani, Luigi; Roethlisberger, Michel
ABSTRACT: Objective: Early permanent cerebrospinal fluid (CSF) diversion for hydrocephalus during the first 2 weeks after aneurysmal subarachnoid hemorrhage (aSAH) shortens the duration of external ventricular drainage (EVD) and reduces EVD-associated infections (EVDAI). The objective of this study was to detect any association with symptomatic delayed cerebral vasospasm (DCVS), or delayed cerebral ischemia (DCI) by the time of hospital discharge. Methods: We used a single-center dataset of aSAH patients who had received a permanent CSF diversion. We compared an 'early group' in which the procedure was performed up to 14 days after the ictus, to a 'late group' in which it was performed from the 15 th day onward. Results: Among 274 consecutive aSAH patients, 39 (14%) had a permanent CSF diversion procedure with a silver-coated EVD. While the blood clot burden was similarly distributed, patients with early permanent CSF diversion (20 out of 39; 51%) had higher levels of consciousness on admission. Early permanent CSF diversion was associated with less colonized catheter, a shorter duration of extracorporeal CSF diversion (OR 0.73, 95%CI 0.58–0.92 per EVD day), and a lower rate of EVDAI (OR 0.08, 95%CI 0.01–0.80). The occurrence of CSF diversion device obstruction, the rate of symptomatic DCVS or detected DCI on computed tomography and the likelihood of a poor outcome at discharge did not differ between the two groups. Discussion: Early permanent CSF diversion lowers the occurrence of catheter colonization and infectious complication without affecting DCVS-related morbidity in good-grade aSAH patients. These findings need confirmation in larger prospective multicenter cohorts. Abbreviations: aSAH: aneurysmal subarachnoid hemorrhage; BNI: Barrow Neurological Institute Scale; CSF: Cerebrospinal fluid; DCVS: Delayed Cerebral Vasospasm; DCI: Delayed Cortical Ischemia; EKNZ: Ethik-Kommission Nordwest Schweiz; EVD: External ventricular drain; EVDAI: External ventricular drain-associated infections; GCS: Glasgow Coma Scale; IRB: Institutional Review Board; IVH: Inraventricular hemorrhage; mRS: Modified Rankin Scale; SOS: Swiss Study of Subarachnoid Hemorrhage Registry; WFNS: World Federation Neurological-Surgeon Scale